Santuario de Kalinga a co-design approach to Dementia management and awareness in the Philippines through a memory care complex - Dacanay, Danna I. (College of Architecture, University of the Philippines Diliman, 2025)
Dementia is considered as one of the most pressing issues in terms of senior citizen healthcare in low to middle income countries (LMICs) such as the Philippines. The lack of standardization, policies, and programs addressing this issue only continue to exacerbate the struggles faced by the people affected by the disease. Pharmacological approaches in treating dementia are effective, but are costly and unsustainable for most Filipino families. The purpose of this study is to serve as a starting point for future research on architectural solutions for dementia in the local context. More specifically, this paper focuses on architecture as the most viable, non-pharmacologic solution to managing dementia symptoms. Unlike previous studies which were statistic-based, this paper aims to provide a more personalized and local approach to dementia care in the country by identifying the current needs of the people affected by the disease by understanding their lived experience through their own, subjective accounts. Using semi-structured interviews with 11 respondents (7 ICG & 4 PCG) and phenomenological analysis for the design concept, it was determined that local dementia facilities should provide the following: community spaces, caregiver support services, ancillary dementia services, and residential dementia care facilities. The results from the study's literature review and respondent input were used to develop the programming for a dementia care complex located in Matandang Balara, Quezon City.